Technological innovation evolution and industrial modernization driven by green factors: Case of combined heat and power (CHP) industry in Yangtze River Delta, China - Su, Chenqing; Wang, Chengsi; Wang, Zhanao; Zhang, Lu; Tian, Yaqi (Frontiers in Environmental Science, 2022)
China’s Yangtze River Delta region has banned the approval of new thermal power projects except for combined heat and power (CHP) generation and is promoting technological innovation in CHP. However, technological innovation of energy technology has been evidenced to be often affected by spatial elements. The role of spatial agglomeration in the energy industry on technological innovation has not been discussed in the context of CHP. Therefore, this article studied the spatial agglomeration and evolution characteristics of CHP technological innovation point elements through the Global Moran's index, kernel density analysis, and thermal map analysis and analyzed the influencing factors and changes by the spatial regression model. The results show that environmental regulation and high-tech park agglomeration are the key factors influencing CHP technological innovation. This indicates that future policy making needs to consider the economic factors of green development and the role of high-tech parks in innovation.